The Regulation of Pyruvate Dehydrogenase Activity in Pea Leaf Mitochondria (The Effect of Respiration and Oxidative Phosphorylation). - Moore, A. L. (1993)
The regulation of the pea (Pisum sativum) leaf mitochondrial pyruvate dehydrogenase complex by respiratory rate and oxidative phosphorylation has been investigated by measuring the respiratory activity, the redox poise of the quinone pool (Q-pool), and mitochondrial pyruvate dehydrogenase (mtPDC) activity under various metabolic conditions. It was found that, under state 4 conditions, mtPDC activity was unaffected by either the addition of succinate, 2-oxoglutarate, or glycine or the overall respiratory rate and redox poise of the Q-pool but was partially inhibited by NADH due to product inhibition. In the presence of ADP significant inactivation of PDC, which was sensitive to oligomycin, was observed with all substrates, apart from pyruvate, suggesting that inactivation was due to ATP formation. Inactivation of PDC by ADP addition was observed even in the presence of carboxyatractyloside, an inhibitor of the ATP/ADP translocator, suggesting that other mechanisms to facilitate the entry of adenylates, in addition to the adenylate carrier, must exist in plant mitochondria.